Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.omto.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA UCA1-Mediated Cdc42 Signaling Promotes Oncolytic Vaccinia Virus Cell-to-Cell Spread in Ovarian Cancer

Abstract: Oncolytic vaccinia virus (OVV) has demonstrated appropriate safety profiles for clinical development. Although designed to kill cancer cells efficiently, OVV sensitivity varies in individual cancers, and predictive biomarkers of therapeutic responses have not been identified. Here we found that OVV was much more efficient in KFTX paclitaxel-resistant ovarian cancer cells compared to that in KFlow paclitaxel-sensitive cells. Microarray analysis identified long non-coding RNA urothelial carcinoma-associated 1 (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Long non-coding RNA urothelial carcinomaassociated 1 (UCA1) employs as an oncogene in different human cancers [6]. LncRNA UCA1 could promote cell growth and migration [7], which owns the potential to be a biomarker for the diagnoses of some cancers [8]. Jiao et al have found that lncRNA UCA1 is a significant molecular for tumor growth and could be an effective target for EC therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNA urothelial carcinomaassociated 1 (UCA1) employs as an oncogene in different human cancers [6]. LncRNA UCA1 could promote cell growth and migration [7], which owns the potential to be a biomarker for the diagnoses of some cancers [8]. Jiao et al have found that lncRNA UCA1 is a significant molecular for tumor growth and could be an effective target for EC therapy [9].…”
Section: Introductionmentioning
confidence: 99%
“…UCA1 is also associated with resistance to Paclitaxel in OC (155,156), which can be reverted by UCA1 knockdown in cell lines (156). This effect was related to reduced sponging of miR-129 and, subsequently down-regulation of the ABCB1 gene that encodes an efflux pump previously correlated with multidrug resistance in cancer (156,157).…”
Section: Lncrnas Involved In Platinum-resistancementioning
confidence: 90%
“… 41 The classification of lncRNAs is based on the idea that RNAs with a base number greater than 200 nt can form various complex high-level structures, which can be distinguished from microRNAs (miRNAs). 42 In fact, however, when the base number of an RNA is 50–70 nt, some complex structures can be formed. 43 In addition to the linear structure, lncRNAs also have circular RNAs, which may be affected by the structure.…”
Section: Main Textmentioning
confidence: 99%